Rancang Bangun Jaringan Internet di Kantor Desa Kerta - Bagaskara, Aditya Caesar; Gede Suhartana, I Ketut (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 2 (2020): JELIKU Volume 9 No 2, November 2020DO - 10.24843/JLK.2020.v09.i02.p19, 2020)
In 2018, the Kerta Village Office in Kerta village, Payangan sub-district, Gianyar district received digital village assistance from the Ministry of Communication and Informatics (Kominfo). The digital village is a central government program to develop communication, especially in rural areas that are still constrained by the internet network. This program is expected to help Kerta villagers to get internet access.